Local Culture as Tourism Attraction of Payakumbuh City - Wimbrayardi Wimbrayardi; Irdhan Epria Darma Putra; Hengki Armez Hidayat; Bambang Parmadi (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2021)
The potential of local culture in tourism development is part of the product of human creativity which has economic value. The research objective is to analyze local culture as a tourism attraction in Payakumbuh City which is packaged in the form of performances, in the pockets of tourist attractions served by junior high school students. The research method used is qualitative analysis through direct observation and in-depth interviews with related parties to the research. To analyze the potential and problems in local culture as a tourism attraction at each research location, including the potential and internal and external problems. Culture, especially in the City of Payakumbuh, in general, has unique potential and a center for art products, namely Sikatuntuang, which can be developed to increase local cultural tourism. The strategy of packaging local culture, especially the art of brush, the city of Payakumbuh, is used as packaging for performing arts that attracts tourists to come to the city Besides being served in pockets of nature tourism in the City of Payakumbuh, there is also a Payakumbuh Fair, which can be used as a media for promotion and introduction of cultural tourism destinations for people in need both nationally and internationally.